Peningkatan Aktivitas dan Hasil Belajar Matematika Siswa Kelas V pada Materi Kelipatan Persekutan Terkecil (KPK) dan Faktor Persekutuan Terbesar (FPB) melalui Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) di SDN 3 Sukajawa Bandar Lampung - Rohelyati, Rohelyati (LPPM STKIP PGRI Bandar Lampung, 2021)
Based on the results of the reflections of class V teachers at SDN 3 Sukajawa, teachers more often use lecture and assignment methods. Teachers have not used innovative and creative approaches, methods, and learning models. This causes students to be less enthusiastic about learning mathematics because they are only passive learning objects and only do assignments given by the teacher. To improve this, the Team Games Tournamet (TGT) type cooperative learning model was chosen. This research is a classroom action research which consists of 2 cycles, each cycle consisting of 3 meetings. The research subjects were teachers (researchers) and fifth grade students of SDN 3 Sukajawa with a total of 36 students. Research colleagues were selected as observers. The variables of this research are Teacher Skills, Student Activities and Learning Outcomes. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that: (1) The skills of the teacher in learning mathematics from the KPK and FPB materials through the application of the Team Game Tournament (TGT) type of cooperative learning model in the first cycle got a score of 27 (good) increased in the second cycle got a score of 31.5 (very good ); (2) Student activities in learning Mathematics on the KPK and FPB material through the application of the Team Game Tournament (TGT) type of cooperative learning model in cycle I got an average score of 17.47 (good) increased in cycle II got a score of 20.29 (good) ; (3) Student learning outcomes in Mathematics learning material KPK and FPB through the application of the Team Game Tournament (TGT) type of cooperative learning model in cycle I got an average score of 68.61 (sufficient) increased in cycle II got a score of 78.06 (good ); (4) Classical completeness of student learning in Mathematics learning material for KPK and FPB through the application of the Team Game Tournament (TGT) type of cooperative learning model in cycle I experienced a classical completeness percentage of 69.4% and in cycle II an increase in the percentage of classical completeness to 83 , 3%. The conclusion of this research is that the quality of learning mathematics material from KPK and FPB through the application of the Team Game Tournament (TGT) type of cooperative learning model in class V SDN 3 Sukajawa has increased. The suggestion from the researcher is that research on the Team Games Tournament (TGT) type of cooperative learning model should not stop here, but can be continued to future research to obtain more accurate results regarding the Team Games Tournament (TGT) type of cooperative learning model.